Evaluating the Ulul Ilmi Model: Enhancing Spiritual and Moral Character through Holistic Islamic Pedagogy in Higher Education - Budiyanti, Nurti; Parhan, Muhamad (Jurnal Pendidikan Islam, 2024)
Purpose – This study evaluates the effectiveness of the Ulul Ilmi model in enhancing the spiritual and moral character of students at Universitas Pendidikan Indonesia. The research addresses gaps in Islamic moral education by integrating spiritual and ethical development into teaching practices, responding to the challenges of moral degradation and limited efficacy of traditional approaches. Design/methods/approach – A quasi-experimental design with pre-test and post-test assessments was employed involving 80 undergraduate students. Data were collected through questionnaires, observations, cognitive tests, and daily spiritual activity forms. The analysis used paired t-tests to measure changes in six dimensions of the Ulul Ilmi character: knowledge, attitude, skill, ethics, social, and spirituality. Findings – The study bridges critical gaps in moral education by introducing and evaluating a comprehensive framework grounded in Islamic principles. The Ulul Ilmi model uniquely addresses knowledge, skills, attitudes, and spirituality, offering an innovative response to contemporary ethical challenges. Research implications – Educational institutions can adopt the Ulul Ilmi model to integrate daily spiritual practices, such as prayer and self-reflection, into curricula. The findings underscore the importance of comprehensive assessment tools to measure and enhance moral education outcomes effectively.